2013
DOI: 10.1002/ppsc.201200111
|View full text |Cite
|
Sign up to set email alerts
|

Metallophilic Bond‐Induced Quenching of Delayed Fluorescence in Au25@BSA Nanoclusters

Abstract: The metallophilic bond is a weak interaction between closed‐shell ions and has been widely used a probe for various sensing of toxic chemicals for environmental safety concerns. Here, the interaction between Au nanoclusters (NCs) and metallic ions (mercury (Hg2+) and copper (Cu2+) ions) is explored using steady‐state and time‐resolved luminescence and transient absorption measurements. For Hg2+ ions, the delayed fluorescence (DF) of bovine serum albumin (BSA) protected Au25 (Au25@BSA) NCs is quenched via an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 51 publications
(52 reference statements)
1
43
0
Order By: Relevance
“…In the case, the pnotoexcited electrons in the singlet excited state transfer into the triplet state (ISC) and then the triplet electrons are effectively trapped by Hg ions; which results selectively in the quenching of the delayed fl uorescence, as shown in Figure 19 . [ 81 ] The timeresolved fl uorescence/absorption measurement confi rms that such an electron transfer results in an anomalous quenching of delayed fl uorescence in Au 25 @BSA ( Figure 20 . Using rate equations, they simulated the dynamic processes and showed a consistent fl uorescence evolution in Au 25 @BSA.…”
Section: Time-resolved Fluorescence and Absorption (Ns-µs)mentioning
confidence: 82%
See 3 more Smart Citations
“…In the case, the pnotoexcited electrons in the singlet excited state transfer into the triplet state (ISC) and then the triplet electrons are effectively trapped by Hg ions; which results selectively in the quenching of the delayed fl uorescence, as shown in Figure 19 . [ 81 ] The timeresolved fl uorescence/absorption measurement confi rms that such an electron transfer results in an anomalous quenching of delayed fl uorescence in Au 25 @BSA ( Figure 20 . Using rate equations, they simulated the dynamic processes and showed a consistent fl uorescence evolution in Au 25 @BSA.…”
Section: Time-resolved Fluorescence and Absorption (Ns-µs)mentioning
confidence: 82%
“…It is interesting to note, an exceptional electron transfer of triplet state was observed by Yu et al through metallophilic bond between Au 25 @BSA and Hg ions. In the case, the pnotoexcited electrons in the singlet excited state transfer into the triplet state (ISC) and then the triplet electrons are effectively trapped by Hg ions; which results selectively in the quenching of the delayed fluorescence, as shown in Figure . The time‐resolved fluorescence/absorption measurement confirms that such an electron transfer results in an anomalous quenching of delayed fluorescence in Au 25 @BSA ( Figure .…”
Section: Optical Properties Of Gold Nanoclustersmentioning
confidence: 83%
See 2 more Smart Citations
“…They observed that, Hg 2+ quenches the delayed fluorescence of BSA Au 25 nanocluster via triplet state electron transfer through metallic bond. However, the Cu 2+ do not alter the delayed fluorescence in BSA Au 25 [18]. There are other numerous reports on the BSA Au clusters for spectroscopic investigations and biochemical applications [2,3,1923].…”
Section: Introductionmentioning
confidence: 99%